Indexing third stream activities in UK universities: exploring the entrepreneurial/enterprising university - David Pickernell (Studies in Higher Education, 2019)
Third Stream Activity (TSA) is increasingly important to UK universities and the wider economy, through innovation and entrepreneurship. Using data from the 2009/2010 UK Higher Education Business and Community Interaction Survey, this study investigates UK universities’ TSA. Throughconsidering the data in original and logged forms, two interpretations of TSA are investigated, in relation to entrepreneurial and enterprising university concepts. Using principle component analysis (PCA) on both data forms, four factors relating to universities’ TSA are identified. A nascent indexing approach is employed to create sub-indexes using the identified factors, weight aggregated to produce final TSA indexes (one for each form of the data). Comparisons are then made betweenrankings of universities using the two versions of TSA index, and subindexes, illustrating differences utilising the entrepreneurial and enterprising university concepts. Important questions are raised forfuture government policy in terms of promoting interventions that drive towards different TSA types